The non-sport dimension of a swimming coach’s work with a potential olympian - Lassek, Bartłomiej (Contemporary problems of physical and health culture, 2022)
The aim of this article is to show pedagogical aspects of coach’s work with athletes and specifically to identify problems which cause athletes to end their sport carriers prematurely. These problems may result from ineffective communication with the coach. There are cases of athletes who despite having a great potential to achieve success in sport, including the Olympic one, will never take part in the Olympic Games. The reason for this may be issues regarding interpersonal relation with a coach. The research results in this article refer to the pedagogical role of a coach from the perspective of 33 athletes representing a swimming club KU AZS Politechnika Łódzka. The introduction covers reasons for addressing the issue as well as theoretical argumentation. Research results show that non-sports dimension of work of the coach with a potential Olympian should be based in effective communication.